Groot ebook - Loveness, Jeff (I Am Groot (2017)., 2016)
Collects Groot #1-6. I am Groot. I AM Groot. I am GROOT. I AM GROOT!!! Translation: For the first time ever, the most famous talking-tree-thing in the Marvel Universe stars in his own series! Life is good for Rocket and Groot, your two favorite Guardians of the Galaxy. They're having a heck of a time on a well-deserved celestial road trip — until Rocket gets raccoon-napped! Taking a leaf out of his feisty, furry friend's book, Groot will have to uproot, branch out alone and em-bark on a cosmic odyssey. He'll face an adventure filled with aliens, sharks, explosions and the Silver Surfer. Far out! Along the way, a world needs saving, and a ship full of mercenaries is cruising for a bruising. Is he the right tree for the job? Well, he is Groot!